Post-concussion Vulnerability to Transient Global Amnesia - Garvey, Matthew D.; Miller, Caitlin J.; Kim, Esther U.; Skulikidis, George; Shetty, Teena (Frontiers in Neurology, 2020)
Few studies have investigated transient global amnesia (TGA) in the context of a concussion and the post-concussion sequelae following TGA. Here we review the case of a 43 year-old male with onset of transient global anterograde and retrograde amnesia 22 days after a sustained concussion. The patient’s head CT, MRI of brain, and EEG were reported normal, and the patient regained full cognitive function 8 hours after the TGA episode, with no recollection of the conspiring events. Following the TGA episode, the patient experienced notable worsening of concussive symptoms, including: headache, head pressure, anxiety, neck pain, feeling slowed down, fogginess, not feeling right, difficulty remembering, and fatigue. The patient remained symptomatic for 32 days after the TGA episode. We suggest a window of post-concussion cerebral vulnerability leading to increased susceptibility to cognitive deficits, such as TGA.